Hemispheric Asymmetries during Processing of Immoral Stimuli - Cope, Lora M.; Schaich Borg, Jana; Harenski, Carla L.; Sinnott-Armstrong, Walter; Lieberman, Debra; Nyalakanti, Prashanth K.; Calhoun, Vince D.; Kiehl, Kent A. (Frontiers in Evolutionary Neuroscience, 2010)
Evolutionary approaches to dissecting our psychological architecture underscore the importance of both function and structure. Here we focus on both the function and structure of our neural circuitry and report a functional bilateral asymmetry associated with the processing of immoral stimuli. Many processes in the human brain are associated with functional specialization unique to one hemisphere. With respect to emotions, most research points to right-hemispheric lateralization. Here we provide evidence that not all emotional stimuli share right-hemispheric lateralization. Across three studies employing different paradigms, the processing of negative morally laden stimuli was found to be highly left-lateralized. Regions of engagement common to the three studies include the left medial prefrontal cortex, left temporoparietal junction, and left posterior cingulate. These data support the hypothesis that processing of immoral stimuli preferentially engages left hemispheric processes and sheds light on our evolved neural architecture.